PENGARUH RASIO KEUANGAN DAN KEPEMILIKAN INSTITUSIONAL TERHADAP DIVIDEND POLICY SERTA IMPLIKASINYA PADA PENGUNGKAPAN CSR - Ayatullah Rehullah Khomeny (Ultima Accounting : Jurnal Ilmu Akuntansi, 2019)
Corporate social responsibility disclosure has an important role for the company as mandated in the annual report by the mandatory disclosure based on Enactment Number 14 in 2007. This research aims to determine and to get empirical evidence about the effect of financial ratios (i.e profitability, debt-to equity ratio) and institutional ownership on the dividend policy and its implications for the corporate social responsibility disclosure. The population in this research are company in manufacturing sub-sectors of automotive and components listed in the Indonesia Stock Exchange in 2013-2017 which using purposive sampling technique is counted 11 companies. Methods of data analysis done by path analysis which comprise the hypothesis testing using Sobel test. These results of this study indicate that debt-to equity ratio and institutional ownership have no direct and indirect effect on the dividen policy and CSR disclosure. Terminable, only profitability has a positive effect on the dividen policy.